The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1080/01652176.2000.9695032
|View full text |Cite
|
Sign up to set email alerts
|

Gauged attenuation of congenital portosystemic shunts: Results in 160 dogs and 15 cats

Abstract: SUMMARYPortosystemic shunts were ligated over a gauged stainless steel rod in 160 dogs and 15 cats, using a midline celiotomy. The diameter of the rod varied with the size of the shunt and the diameter of the portal vein cranial to the shunt. Shunts were narrowed to the smallest diameter that did not cause signs of portal hypertension such as cyanosis of the stomach, pancreas, and small intestine. A slight discoloration was accepted only if the heart rate, end-expiratory CO2%, or arterial blood pressure (if av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
117
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(123 citation statements)
references
References 9 publications
3
117
1
Order By: Relevance
“…Surgical approaches for CPSS carry a high mortality risk because of postsurgical hypertension, coagulopathies because of impaired liver function, and anesthetic problems related to central neurotransmitter imbalances. 5,6,10,11 Moreover, long-term effects reported to occur in surviving dogs are due to inadequate growth of the portal vascular system resulting in permanent postsurgical portal hypertension. 5,6,23 Recently, in a nonrandomized study of dogs with CPSS, dietary management appeared to have comparable long-term success as surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical approaches for CPSS carry a high mortality risk because of postsurgical hypertension, coagulopathies because of impaired liver function, and anesthetic problems related to central neurotransmitter imbalances. 5,6,10,11 Moreover, long-term effects reported to occur in surviving dogs are due to inadequate growth of the portal vascular system resulting in permanent postsurgical portal hypertension. 5,6,23 Recently, in a nonrandomized study of dogs with CPSS, dietary management appeared to have comparable long-term success as surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The ameroid constrictor has been shown to result in shorter surgery times and less complication than other surgical approaches. [6][7][8][9] One of the complicating factors is the high anesthetic risk because of central neurotransmitter dysfunction mainly associated with hyperammonemia. [10][11][12] Decreased production of clotting factors causes coagulopathy as an additional risk factor at surgery.…”
mentioning
confidence: 99%
“…When there is hypoplasia of the portal venous circulation cranial to the shunt, the CPS is closed to the maximum degree of attenuation (partial ligation) that can be tolerated without fatal portal hypertension. [3][4][5][6][7] An alternative method is to use surgical techniques that achieve gradual progressive closure of the CPS such as perivascular ameroid constrictors, cellophane banding, and intravascular thrombogenic coils. [8][9][10][11][12][13][14][15] The prognosis after surgical intervention remains unpredictable and recurrence or persistence of clinical disease has been documented with all techniques used for shunt attenuation.…”
mentioning
confidence: 99%
“…Two months after surgery the patency of the shunting vessel, which was left open partially during surgery, was tested with echo-Doppler examination and ammonia tolerance tests. 6 These tests showed that there was no remaining functional portosystemic shunting in any of the 3 littermates. The dogs were fed a standard commercial dog food and were further kept as companion animals in the foster families.…”
Section: Parentsmentioning
confidence: 99%
“…1,4,5 Both parents were unaffected, but the 6 offspring included 1 affected male, 2 affected females, and 3 unaffected males. All 3 affected dogs were treated successfully by surgical attenuation of the shunt 6 at an age of 3-4 months.…”
Section: Parentsmentioning
confidence: 99%